2009
DOI: 10.5433/1679-0359.2009v30n2p447
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do pH e da eletrocondutividade do leite de bovinos da raça Jersey durante o primeiro mês de lactação

Abstract: ResumoCom o objetivo de avaliar a influência do período colostral no pH e na eletrocondutividade foram colhidas 418 amostras de leite provenientes de mamas sadias de 127 vacas da raça Jersey e que não apresentem crescimento bacteriano no exame microbiológico. As amostras foram divididas em oito grupos a seguir discriminados: < 1/2 dia; 1/2 a 1º dia; 2º dia; 3º dia; 4º e 5º dia; 6º e 7º dia; 8º ao 15º dia; 16ºao 30º dia em lactação.As amostras foram colhidas antes da ordenha, sendo as seguintes determinações re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
0
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
2
0
0
2
Order By: Relevance
“…The authors found compliance with legislation regarding fat content; however, protein values, freezing point and titratable acidity of pasteurized milk were in disagreement with current legislation. The average pH value of milk in this study is in agreement with the pH results recorded for (6.32 to 6.75) by Raimondo et al (2009). The physicochemical parameter recorded for milk whey (fat, 0.4%; protein, 2.66%; acidity, 0.11 g of lactic acid/100 mL and pH, 6.44) in the present study (Table 1) is comparable with physicochemical characteristics studied for milk whey by Teixeira and Fonseca (2008).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The authors found compliance with legislation regarding fat content; however, protein values, freezing point and titratable acidity of pasteurized milk were in disagreement with current legislation. The average pH value of milk in this study is in agreement with the pH results recorded for (6.32 to 6.75) by Raimondo et al (2009). The physicochemical parameter recorded for milk whey (fat, 0.4%; protein, 2.66%; acidity, 0.11 g of lactic acid/100 mL and pH, 6.44) in the present study (Table 1) is comparable with physicochemical characteristics studied for milk whey by Teixeira and Fonseca (2008).…”
Section: Resultssupporting
confidence: 90%
“…The physicochemical parameter recorded for milk whey (fat, 0.4%; protein, 2.66%; acidity, 0.11 g of lactic acid/100 mL and pH, 6.44) in the present study (Table 1) is comparable with physicochemical characteristics studied for milk whey by Teixeira and Fonseca (2008). The average pH value of milk in this study corroborates results by Raimondo et al (2009) with variations from 6.32 to 6.75.…”
Section: Resultssupporting
confidence: 89%
“…O pH da amostra de leite aos 15 dias de lactação diferiu estatisticamente das amostras coletadas com 6, 12 e 18 meses de lactação. Os resultados obtidos foram semelhantes aos citados por Raimondo et al (2009), que, pesquisando as características físico-químicas de leites em diferentes dias de lactação, obtiveram aumento nos valores de pH de 6,37 (12 horas de lactação) a 6,71 (30 dias de lactação). Segundo Venturini et al (2007), o pH do leite recém-ordenhado de uma vaca sadia pode variar entre 6,4 a 6,8 e também pode ser um indicador da qualidade sanitária e da estabilidade térmica do leite.…”
Section: Resultsunclassified
“…As vacas com mastite assintomática ou clínica apresentaram valores de células somáticas superiores aos sadios ao longo de todo o período experimental (Tabela 1), porém, com o passar do tempo, houve a diminuição gradativa média de tais valores, o que também foi observado por Godden (2008); Maunsell et al (1999); Birgel Junior (2006); Raimondo et al (2008). Maunsell et al (1998) reportaram valores médios de células somáticas para animais sadios no pós-parto de 891.000 células/mL e em animais da raça Holandesa , que pariram com mastite clínica, encontraram valores médios de 4413x10³/mL, o que difere dos valores apresentados no presente trabalho.…”
Section: Discussionunclassified